TEACHER ADAPTABILITY: A SCOPING REVIEW OF CONCEPTUALISATIONS AND MEASUREMENT INSTRUMENTS - Ruby, Arcivid Chorynia (International Journal of Instructions and Language Studies, 2026)
Teacher adaptability has become increasingly salient as school systems navigate curriculum reform, digitalisation and post-pandemic recovery. In this review, it is defined as the capacity to adjust cognition, affect, and behaviour in response to changes. This scoping review maps how teacher adaptability is conceptualised and which measurement instruments have been used in school-related literature, along with the technical characteristics and psychometric evidence reported for those instruments. Guided by PRISMA-ScR, systematic searches of PubMed, Scopus, Web of Science, and ERIC were conducted on 5 January 2026 and supplemented by citation tracking of included and foundational sources. From 300 records, 50 duplicates were removed, 250 titles and abstracts were screened, 50 full-text sources were assessed for eligibility, and 25 sources were included in the final evidence map. Across the reviewed sources, teacher adaptability was conceptualised most consistently as a triadic capacity for cognitive, affective, and behavioural adjustment to change. Measurement was dominated by brief self-report instruments derived from the same conceptual tradition, with psychometric reporting focused on internal consistency and model-based validity evidence. Secondary descriptive patterns indicated that these instruments were used most often in school-based job demands–resources research, crisis-era and online teaching research, and beginning-teacher or teacher-educator contexts. As an international evidence map, this review clarifies construct boundaries, dominant measurement patterns, and priority directions for future validation across contexts.